Microstructural evolution and B2 ordering in a new CuPdAgRu alloy - Kuglstatter, Moritz; Karpstein, Nicolas; Apeleo Zubiri, Benjamin; Wu, Mingjian; Fecher, Jonas; Spiecker, Erdmann; Höppel, Heinz Werner; Göken, Mathias (Scripta Materialia, 2026)
Recently, it has been reported that the formation of B2 crystals in CuPdAgRu alloys leads to a notable increase in strength and conductivity. Here, we investigate the microstructural evolution associated with the formation of the ordered B2 phase: Correlative X-ray and electron diffraction analysis confirms the partial transformation of the initial fcc structure of the alloy into B2; the distribution of alloying elements within the latter phase is revealed by atomic-scale energy-dispersive X-ray spectroscopy. 4D-STEM virtual dark-field imaging uncovers a finely and homogeneously distributed B2 phase. High-resolution STEM imaging directly reveals few-nanometer thin plate-like regions of fcc remaining embedded coherently in the B2 matrix with a specific orientation relationship; these regions correlate with an enrichment of Ag and depletion of Cu, contributing to the large lattice misfit between both phases. These observations provide insights into microscopic-level structural changes and their possible influence on macroscopic properties of advanced functional alloys.
CRIS-Team Scopus Importer:2025-11-21
Keywords: 4D-STEM; Intermetallic phases; Orientation relationship; Transmission electron microscopy; X-ray diffraction